Moderating effect of speed desire frustration on the relationship between driving stress and coping behavior on traffic accident risk - Lee, SoonYeol; Lee, SoonChul (Korean Journal of Industrial and Organizational Psychology, 2012)
The present study was conducted to determine the effects of driving stress on traffic accident risk. Specifically, the study verified whether a driver’s speed desire frustration plays a control role in the relations between driving stress and traffic accident risk. As a result, a driver’s speed desire frustration level played a control role in the relation between driving stress and traffic accident risk. This indicates that a driver’s speed desire frustration level change driving stress sensitivities, thus changing the effects of selecting coping behavior types and causing differences in total traffic accident risk. The results show that the mere concentration on driving stress management cannot sufficiently lower the traffic accident risks caused by driving stress. This is because driving stress have indirect influences on traffic accident risk. Hence, it will be necessary to seek how to reduce driving stress and control coping behavior types in order to lower the traffic accidents risk by the stress.